Structural and Functional Features of Comparison Methods in the Yakut and Khakass Epics - Gerasimova, Liliya Nikolaevna; Lvova, Sakhaya Danilovna (Journal of History Culture and Art Research, 2018)
In the article, an attempt of comparative analysis is made between the texts of two different Turkic epics (the Yakut Olonkho “Kyys Debiliye” and the Khakass alyptic nymakh “Ay Huuchin”) that were published in the academic series “Monuments of folklore of the peoples of Siberia and the Far East”. The choice of these texts is determined by the scientific nature of the publications, the belonging of these epics to one type of women-heroes tales, the presence of a Russian translation, and their relatively equal volume. The relevance of the study is determined by the growing interest for comparative study of the language and epic poetics, as well as their genesis. The purpose of this article is to establish the features in the methods of comparison formation in the Yakut and Khakass epics. The study of comparison is always in demand as an artistic and pictorial tool in linguistics and folklore studies. The subject of this study is the syntactic comparison structures, previously identified from the texts of the epics that were questioned by the method of continuous sampling. The methodology practiced by Yu.I. Vasiliev in the Yakut and E.V. Kyrzhinakova in the Khakass languages were used to study the comparisons and classifications. The study leads to conclusion that the comparison in the Yakut epic is expressed mainly by lexical means (the indicator of comparison are function and categorematic words), and in Khakass – lexical and morphological words (with the help of derivational and case affixes). The most common way of forming a comparison in the Yakut olonkho is the method with the help of the курдук index ‘alike, similar to, as’, and in Khakass alyptic nymakh – with the word чiли ‘like, akin to’. Words with a same etymology were not established among the lexical indicators of the two epics. The common ancient Turkic origin have two morphological indicators: the affix -ча and the affix of the ablative case. A relative analysis of comparative works revealed that there are no completely identical structures in epic texts, but comparisons with similar objects and images, decorated with the help of various indicator words and affixes, are noted. A number of comparable works have a commonality in the expression of the same features and functions. Further studying of the comparative formations with the involvement of a wider material, including other Turkic epics is for seen.